2013
DOI: 10.1080/10942912.2011.565902
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant and Antihemolytic Activities of Hydroalcoholic Extracts of Allium scabriscapum Boiss. & Ky. Aerial Parts and Bulbs

Abstract: This study is designed to evaluate the antioxidant and antihaemolytic activities of the hydroalcoholic extracts of Allium scabriscapum aerial parts and bulbs by employing eight in vitro assay systems. In 1,1-diphenyl-2-picryl hydrazyl radical scavenging assay, both the extracts show moderate scavenging activity. The reducing power ability of extracts increased with increasing in the samples concentrations. IC 50 for metal chelating activity of aerial parts and bulbs extracts were 894.6 ± 31.29 and 746.2 ± 26.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The total flavonoid content (TFC) was determined colorimetrically according to the method described by Nabavi, Nabavi, Ebrahimzadeh, Eslami, and Jafari () with slight modifications. An aliquot of 30 µL extracts in methanol was sequentially mixed with 90 µL of methanol, 6 µL of 10% aluminum chloride, 6 µL of 1 M potassium acetate, and 168 µL of double distilled water, followed by incubation in the dark at room temperature for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The total flavonoid content (TFC) was determined colorimetrically according to the method described by Nabavi, Nabavi, Ebrahimzadeh, Eslami, and Jafari () with slight modifications. An aliquot of 30 µL extracts in methanol was sequentially mixed with 90 µL of methanol, 6 µL of 10% aluminum chloride, 6 µL of 1 M potassium acetate, and 168 µL of double distilled water, followed by incubation in the dark at room temperature for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…During past two decades, a plethora of scientific evidences showed that natural products especially plants and their polyphenolic compounds have different beneficial effects on human health (Del Rio et al, 2013;Pandey and Rizvi, 2009;Scalbert et al, 2005;Visioli et al, 2011). Among them, flavonoids known as the most important bioactive compounds which have beneficial effects on different cancerous tissues (Chahar et al, 2011;Nabavi et al, 2013a;Spatafora and Tringali, 2012). Several epidemiological studies indicate an inverse association between flavonoids intake in diet and risk of cancers (Romagnolo and Selmin, 2012;Somerset and Johannot, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Recent research has been focused on the promising effects of antioxidants for the treatment of various diseases (Newman and Cragg, 2012;Gullett et al, 2010;Wang et al, 2012). Nowadays, much attention has been paid to natural antioxidants due to their high efficacy and low adverse effects in comparison with synthetic antioxidants (Alinezhad et al, 2013;Nabavi et al, 2012Nabavi et al, , 2015Nabavi et al, , 2014Nabavi et al, , 2013a. During past two decades, a plethora of scientific evidences showed that natural products especially plants and their polyphenolic compounds have different beneficial effects on human health (Del Rio et al, 2013;Pandey and Rizvi, 2009;Scalbert et al, 2005;Visioli et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Briefly, the antioxidant activity of A. atroviolaceum , [24] A. schoenoprasum , [25] A. scorodoprasum subsp. rotundum , [24] A. tripedale , [24,26] and A. scabriscapum [27] were evaluated. The antimicrobial activity of A. atroviolaceum , [18] A. schoenoprasum , [25] and A. tripedale , [28] and the antihemolytic activity of A. scabriscapum , [27] and the α‐amylase inhibitory activity [29] of A. akaka were also investigated.…”
Section: Introductionmentioning
confidence: 99%